The attraction of evil. An investigation of factors explaining women’s romantic parasocial relationships with bad guys in movies and series - Schramm, Holger; Sartorius, Annika (Frontiers in Psychology, 2024)
The attractiveness of bad boys can be seen as a cultural phenomenon that can be found in different areas of society and art. In the media, too, the bad boy fulfills social expectations in terms of masculinity and is often portrayed as dominant, violent, hard, unemotional and aggressive. Women may feel attracted to this male dominance under certain conditions. In order to investigate this phenomenon in the field of media psychology, this study examined women’s personality as predictor of romantic parasocial relationships (RPSR) with bad boys from movies or series, as well as feelings and experiences associated with such relationships. In an online questionnaire, 47 women were asked about specific personality traits, their RPSR with their favorite bad boy, and their perceived egocentric feelings and experiences associated with this RPSR. Both the love style ludus, which describes unattached playful love, and sensation seeking, which encompasses a woman’s inclination towards new experiences and adventures, emerge as predictors of an RPSR to a bad boy. Furthermore, it was found that a woman’s RPSR to a bad boy goes along with her retrospective imaginative involvement and sense of power. The findings show parallels to findings from social psychology that explain the attractiveness of bad boys in real relationships. Due to its correlative design, the study should be seen as a first step in the exploration of this media-psychological phenomenon, which will hopefully be followed by further studies with a stricter causality logic.